2013
DOI: 10.1159/000351068
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Sensitization to <b><i>Cannabis sativa</i></b>. Lipid-Transfer and Thaumatin-Like Proteins Are Relevant Allergens

Abstract: Background: Although allergy to Cannabis sativa was first reported over 40 years ago, the allergenicity has scarcely been studied. The objectives of this study were to investigate the frequency of sensitization to this plant, to analyze the clinical characteristics and allergenic profile of sensitized individuals and to identify the allergens involved. Methods: Five hundred and forty-five individuals in Spain attending allergy clinics with respiratory or cutaneous symptoms underwent a skin-prick test (SPT) wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
47
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 21 publications
1
47
0
1
Order By: Relevance
“…In our series, a positive industrial hemp sIgE test was observed in all 12 cannabis allergic patients but unfortunately also in 3 out of 8 pollen allergic patients without cannabis allergy (Ebo et al 2013). Using a whole protein extract, Larramendi et al (2013) found a positive sIgE result to a native cannabis extract in 21 out of 32 individuals who had their cannabis sensitization documented by a positive cannabis skin test. Herzinger et al (2011) found positive sIgE results to marihuana and/or hashish in two patients with professional exposure to cannabis.…”
Section: Diagnosissupporting
confidence: 43%
See 3 more Smart Citations
“…In our series, a positive industrial hemp sIgE test was observed in all 12 cannabis allergic patients but unfortunately also in 3 out of 8 pollen allergic patients without cannabis allergy (Ebo et al 2013). Using a whole protein extract, Larramendi et al (2013) found a positive sIgE result to a native cannabis extract in 21 out of 32 individuals who had their cannabis sensitization documented by a positive cannabis skin test. Herzinger et al (2011) found positive sIgE results to marihuana and/or hashish in two patients with professional exposure to cannabis.…”
Section: Diagnosissupporting
confidence: 43%
“…Although in the study of Larramendi et al (2013), no homology was found between the 14-kDa band and any known allergen, it was speculated that this band could be a profilin (de Larramendi et al 2008).…”
Section: Cannabis Allergensmentioning
confidence: 97%
See 2 more Smart Citations
“…Few true IgE-dependent allergic reactions in illicit abusers have been published (7)(8)(9)(10) making it hard to determinate the true prevalence of this allergy. Nevertheless, multiple reports on cutaneous and respiratory allergies to different members of the Cannabaceae family like industrial hemp and hop (Humulus lupulus) have been published (11)(12)(13)(14)(15).…”
Section: Prevalencementioning
confidence: 99%